Rap Music, Department Image and Student Intention; A Study in Japan - BìnhNghiêm- Phú (Universitas Riau, 2019)
In the education context, the majority of studies on student intentions (school selection, retention and dropout) focused on the internal affecting factors (e.g., sex, family background, school performance and satisfaction). Those on the external determinants (e.g., school image) seem to be too thin, although these factors can be more easily and effectively regulated by education institutions. School image, however, does not stay unchanged but revolves over time. Nevertheless, the instability of school image has not been examined by previous research. Based on these understandings, this study aims to examine the change of a school department’s images with the input of rap music as an image change agent. In addition, it investigates the correlation between department images and student intentions. Using the quantitative data collected from 96 students in three low-grade classes (1-3) in a junior technology college in the Tohoku region of Japan, this study found that the impacts that a piece of rap music can produce is marginally limited, and the images of the department are decaying. In addition, the study figured out that department images are significant to the formation of students’ intentions to go to the advanced course and to recommend the department, but don’t have any significant effect on students’ intention to finish their five-year study. Some implications for the management of education activities to retain and recruit students are proposed based on these outcomes.